2002
DOI: 10.1136/jms.9.2.86
|View full text |Cite
|
Sign up to set email alerts
|

The cervical cancer screening programme in Norway, 1992–2000: changes in Pap smear coverage and incidence of cervical cancer

Abstract: The coordinated screening programme provides a low cost way of increasing the coverage of the female population, and consequently has reduced the rate of invasive cervical cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
111
0
12

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(124 citation statements)
references
References 21 publications
1
111
0
12
Order By: Relevance
“…Several studies demonstrated that cervical canser screening by Pap test reduces mortality rates. (Nygard et al, 2002;Abed et al, 2006;Aklimunnessa et al, 2006;Taylor et al, 2006). Currently, there is no organized population-based screening program available for the whole World.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated that cervical canser screening by Pap test reduces mortality rates. (Nygard et al, 2002;Abed et al, 2006;Aklimunnessa et al, 2006;Taylor et al, 2006). Currently, there is no organized population-based screening program available for the whole World.…”
Section: Discussionmentioning
confidence: 99%
“…In the Norwegian screening programme, the relative risk of CIN2+ within 2 years after an ASCUS diagnosis compared with women with a negative result was 15 to 30. 38 In the ASCUS LSIL Triage Study (ALTS) trial, the 24-month cumulative incidence of CIN3+ among women with an index smear showing ASCUS varied between 8 and 9%. 39 In a meta-analysis of the diagnostic performance of management methods for women with a prior ASCUS result, the pooled prevalent risk of CIN2+ was 10% and the risk of CIN3+ was 6%.…”
Section: Management Of Women With Atypical Squamous Cellsmentioning
confidence: 99%
“…The most common cervical cancer screening method, the Papanicolaou (Pap) cervical cytology screening, has been proven to reduce cervical cancer rates dramatically through early detection of premalignant lesions (Devesa et al, 1997;Nygard et al, 2002).…”
Section: Introductionmentioning
confidence: 99%